Perceptions of inclusion among lower secondary level students in Finland - Kyttälä Minna; Sinkkonen Hanna-Maija; Harju-Autti Raisa (Routledge, Taylor & Francis Group, 2025)
This study aims at investigating Finnish lower secondary grade students’ (N = 469) emotional school well-being, social inclusion, and academic self-concept with regard to grade level, linguistic background, and needs for support. For collecting the data, a Finnish translation of the Perceptions of Inclusion Questionnaire for students was used. The results suggest that, considering the students’ own perceptions, Finnish schools are quite inclusive with regard to students’ linguistic backgrounds. Although the results showed a decrease in emotional well-being, social inclusion, and academic self-concept during the lower secondary level, this decrease was not related to any specific background factors. The results indicate that students receiving support showed lower levels of social inclusion and academic self-concept, suggesting that not all students feel equally included. These findings underline the importance of assessing students’ own perceptions of inclusion. Additionally, educational implications are discussed.